2007
DOI: 10.1017/s0033291707001614
|View full text |Cite
|
Sign up to set email alerts
|

A meta-analysis of randomized trials of behavioural treatment of depression

Abstract: Use policyThe full-text may be used and/or reproduced, and given to third parties in any format or medium, without prior permission or charge, for personal research or study, educational, or not-for-pro t purposes provided that:• a full bibliographic reference is made to the original source • a link is made to the metadata record in DRO • the full-text is not changed in any way The full-text must not be sold in any format or medium without the formal permission of the copyright holders.Please consult the full … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
277
0
12

Year Published

2009
2009
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 349 publications
(301 citation statements)
references
References 41 publications
12
277
0
12
Order By: Relevance
“…The effectiveness of this psychological approach is now well demonstrated. 27 Behavioural activation can be readily delivered by a trained case manager either over the telephone or face to face for those who experience difficulty using or accessing telephone-based therapy. 28 …”
Section: Rationale For the Casper Trialmentioning
confidence: 99%
“…The effectiveness of this psychological approach is now well demonstrated. 27 Behavioural activation can be readily delivered by a trained case manager either over the telephone or face to face for those who experience difficulty using or accessing telephone-based therapy. 28 …”
Section: Rationale For the Casper Trialmentioning
confidence: 99%
“…For example, behavioural activation (BA), whereby activity scheduling is used to increase the individual's exposure to rewarding stimuli in order to lift mood, has well-established efficacy in the treatment of depression (Cuijpers, van Straten, & Warmerdam, 2007;Ekers, Richards, & Gilbody, 2008;Mazzucchelli, Kane, & Rees, 2009), and may be just as effective as more complex CBT interventions (Jacobson et al, 1996). A pilot study trialling BA for psychosis (Mairs, Lovell, Campbell, & Keeley, 2011) reported promising results from 8 patients indicating feasibility, treatment adherence and initial outcomes: non-significant improvements in depression, positive symptoms and negative symptoms.…”
Section: Depression-related Interventions For People With Psychosismentioning
confidence: 99%
“…In the cognitive model, Beck and his colleagues 6 posit that decreased maladaptive cognitions mediate symptom alleviation, whereas in Lewinsohn's behavioral model, 7 increased contact with reinforcing environmental contingencies (i.e., behavioral activation) results in symptom improvement. Recent mediational and component analyses have yielded support for both behavioral 8,9 and cognitive 10--13 mechanisms of change in the amelioration of mood symptoms; however, several studies investigating the relative importance of This document has undergone peer review. This is a non-final version of an article published in final form in Journal of Psychiatric Practice:…”
Section: Introductionmentioning
confidence: 99%